Renal Morpho-functional Changes in Wistar Rats Administered Citrullus lanatus (Watermelon) - , A. A. Aigbiremolen; , M. A. Omoirri; , O. J. Okafoanyali; , M. Ogbonnaya; , K. E. Asemota (Archives of Current Research International, 2019)
Introduction: The kidneys are paired organs that function as eliminators of harmful metabolites from the blood. Considering the nutritional profile, Citrullus lanatus is reportedly a vital source of anti-oxidants that may affect renal functions. Aim: Using the adult male wistar rats, this study examined the effect(s) of Citrullus lanatus fruit seeds on serum electrolytes and histology of the kidney. Methodology: Twenty rats (95-200 g) were purchased and grouped into four (n=20) of five (5) rats per group. Group 1 (control group) received growers mash and water only, groups 2, 3 and 4 were fed with 100, 200 and, 400 mg/kg of C. lanatus fruit seeds extract respectively (for 21 days). Following period of extract administration, animals were fasted overnight and carefully restrained. Equal volume of blood samples were collected from their retro-orbital plexus for biochemical analysis. Abdominal cavities were cut opened and kidney excised for histo-architectural study. Results: With serum Na+, Cl-, Ca2+, HCO3- , levels returning insignificant results for all doses (100 mg/kg, 200 mg/kg and 400 mg/kg) of watermelon fruit seed extracts treated rats upon comparison with control; there was however a significant increase (p < .05) in serum K+ and Urea levels of extract treated rats when compared with control. Study also observed no histological alteration in the kidney of extract treated rats when compared to control. Conclusion: Thus, administration of C. lanatus seed extract did not affect serum Na+, Cl-, HCO3- and creatinine levels of wistar rats; even though there were significance increase in K+ and urea levels.